A Novel CLN6 Variant Associated With Juvenile Neuronal Ceroid Lipofuscinosis in Patients With Absence of Visual Loss as a Presenting Feature - Nicolaou, Paschalis; Tanteles, George A.; Votsi, Christina; Zamba-Papanicolaou, Eleni; Papacostas, Savvas S.; Christodoulou, Kyproula; Christou, Yiolanda-Panayiota (Frontiers in Genetics, 2021)
The neuronal ceroid lipofuscinoses (NCLs), also known as Batten disease, are a group of autosomal recessive lysosomal storage disorders that are characterized by neurodegeneration, progressive cognitive decline, motor impairment, ataxia, loss of vision, seizures, and premature death. To date, pathogenic variants in more than 13 genes have been associated with NCLs. CLN6 encodes an endoplasmic reticulum non-glycosylated transmembrane protein, which is involved in lysosomal acidification. Mutations in CLN6 cause late-infantile juvenile NCL (JNCL) adult-onset NCL, and Kufs disease. Members from two available families with JNCL were clinically evaluated, and samples were collected from consenting individuals. The molecular investigation was performed by whole-exome sequencing, Sanger sequencing, and family segregation analysis. Furthermore, in silico prediction analysis and structural modeling of the identified CLN6 variants were performed. We report clinical and genetic findings of three patients from two Greek-Cypriot families (families 915 and 926) with JNCL. All patients were males, and the first symptoms appeared at the age of 6 years. The proband of family 926 presented with loss of motor abilities, ataxia, spasticity, seizure, and epilepsy. The proband of family 915 had ataxia, spasticity, dysarthria, dystonia, and intellectual disability. Both probands did not show initial signs of vision and/or hearing loss. Molecular analysis of family 926 revealed two CLN6 biallelic variants: the novel, de novo p.Tyr295Cys and the known p.Arg136His variants. In family 915, both patients were homozygous for the p.Arg136His CLN6 variant. Prediction analysis of the two CLN6 variants characterized them as probably damaging and disease-causing. Structural modeling of the variants predicted that they probably cause protein structural differentiation. In conclusion, we describe two unrelated Cypriot families with JNCL. Both families had variants in the CLN6 gene; however, they presented with slightly different symptoms, and notably none of the patients has loss of vision. In silico prediction and structural analyses indicate that both variants are most likely pathogenic.